Student Loan Debt Does Not Predict Female Physicians’ Choice of Primary Care Specialty - Frank, Erica (Blackwell Science Inc, 1999)
OBJECTIVE: There has never been a conclusive test of whether there is a relation between ultimately choosing to be a primary care physician and one’s amount of student loan debt at medical school graduation. DESIGN/SETTING/PARTICIPANTS: To test this question, we examined data from the Women Physicians’ Health Study, a large, nationally representative, questionnaire-based study of 4,501 U.S. women physicians. MEASUREMENTS AND MAIN RESULTS: We found that the youngest physicians were more than five times as likely as the oldest to have had some student loan debt and far more likely to have had high debt levels (p < .0001). However, younger women physicians were also more likely to choose a primary care specialty (p < .002). There was no relation between being a primary care physician and amount of indebtedness (p = .77); this was true even when the results were adjusted for the physicians’ decade of graduation and ethnicity (p = .79). CONCLUSIONS: Although there may be other reasons for reducing student loan debt, at least among U.S. women physicians, encouraging primary care as a specialty choice may not be a reason for doing so.